Habitus and Capital in the Gastronomy Tourism Field: Cooking Class Businesses in Ubud, Bali - Ni Nyoman Sri Aryanti; Eni Harmayani; Wening Udasmoro; Dyah Mutiarin (Centre of Excellence in Tourism Udayana University, 2025)
This study examines the practice of cooking class businesses as a form of gastronomic tourism attraction in Ubud, Bali. Cooking classes have rapidly expanded in this destination, yet attention to how they shaped by cultural practice and local strategies of capital conversion remains limitedly researched. Drawing on Pierre Bourdieu’s theory of practice, it analyzes how entrepreneurs and instructors mobilize and position their economic, cultural, and social capital within the tourism field. A qualitative approach was employed, combining participatory and non-participatory observation conducted at some cooking class sites in Gianyar Regency particularly at Ubud area and in-depth interviews to their owners or instructors. Data were analyzed through Bourdieu’s concepts of Habitus, Capital, and field to trace how practices emerged and are sustained. The findings reveal that cooking class practices are shaped by the interplay between habitus and various forms of capital. Cultural practices such as mebat (communal food preparation) and ngelawar(family cooking traditions) rooted in the socio-cultural and domestic fields serve as key sources of cultural and social capital. These resources are transformed and recontextualized into economic capital, enabling local actors to compete and gain recognition in the tourism field. The study shows that gastronomic tourism in Ubud, Gianyar is not only about economic gain but also about turning local knowledge and traditions into tourism experiences. Cooking classes serve as space for preserving culture, sharing community values, and provide local people to improve their livelihoods. The findings also underline the importance of support and policies that build local capacity while maintaining the authenticity of Balinese gastronomic heritage.